AB0399 Eular recommendations for the management of rheumatoid arthritis: Do we all agree?. (23rd January 2014) - Cunha-Miranda, L.; Rodrigues, C.; Fernandes, S.
Abstract : Background: Over the past 15 years, rheumatologists have developed and witnessed many paradigmatic changes in the treatment of rheumatoid arthritis (RA). In RA, joint damage and physical disability are the major adverse outcomes associated with reduction in quality of life and premature mortality. Some inconsistencies in therapeutic targets and strategies among rheumatologists have been recognised. EULAR published the "EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs". But what is the real impact on clinician's daily practice of these guidelines. Objectives: To assess Portuguese Rheumatologists' opinion on the "EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs" published in May 2010. The opinion from 52 experts regarding the 15 recommendations published this year by the EULAR, is presented at table 1 . When assessing the potential impact of these recommendations, 62% of the experts considered these recommendations important to their practice, nevertheless 61% of the present rheumatologists said that they wouldn't change their common daily practice Conclusions: Although there is an overall agreement in most of the recommendations, there are some that are not so consensual. Although the Portuguese rheumatologists considered them important, they wouldn't change their clinical practice after this publication. This may reflect the gap between EULAR recommendations and real life practice. A greater involvement of all countries that constitute the EULAR is needed, so that different sensibilities and expertises are covered. References: Smolen JS et al. Ann Rheum Dis 2010;69:631-7. Smolen JS et al. Ann Rheum Dis 2010;69:964-75. Disclosure of Interest: None Declared